The Phenomenology of Sensitive Mother-to-Children Disclosure of Divorce Concerns - Fazilat-pour, Vahideh; Gholamzadeh-Jofreh, Maryam; Nazarifar, Mohsen (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of the current research is to explore the experience of self-disclosure by divorced mothers about the issue of divorce to their children. Method: In this qualitative study, a semi-structured in-depth interview was conducted with a purposive sample consisting of 22 divorced mothers with at least one child aged 10 to 38 years. Data analysis through Colaizzi's method led to the discovery of two main categories: self-disclosure topics and factors influencing them. Results: Key topics raised include: expressing the reason for the divorce, decision-making about the imminent divorce, and problems arising after the divorce. Some of the influential factors on these self-disclosures include the age and gender of the child, and the mother's beliefs. The results indicate that the stresses related to divorce make mothers more prone to negative self-disclosure towards their children. Conclusion: Therefore, greater attention by mothers to the occurrence of this phenomenon in their interactions with children and the use of specialized counseling services can reduce the negative consequences of divorce.